(untitled) (Indian Journal of Animal Production and Management, 2024)
The present investigation was carried out to investigate the milk composition, fatty acid profile, vitamins, and antioxidants and association of stage of lactation with milk components. For this study, we collected 100 ml milk from 50 lactating Malvi cattle at Livestock Research Station, Dag Jhalawar. Jhalawar is situated in a humid region of Rajasthan. Representative milk samples were collected and brought to the laboratory. In the Analysis of Variance, the statistical difference for TAC between different stages of lactation was found significant (p<0.05) and PSA was highly significant (p<0.01) for Malvi cattle. The analysis of variance revealed a significant effect of stage of lactation on Retinol, and vitamin C, and a non-significant effect on vitamin E. The analysis of variance found a highly significant (P<0.01) effect of stage of lactation on SFA, MUFA, Omega-6, and Omega-9 whereas non- significant on PUFA and Omega-3. Present study concludes that the lactation has a significant effect on vitamins, fatty acid profile, total antioxidant capacity and free radical scavenging activity in milk of Malvi cattle.